SVALBARD: FRONTIERA ARTICA - Paolo Sellari (Bollettino della Società Geografica Italiana, 2019)
The uncertain history of settlements, the significance of the Treaty of 1920, the geostrategic position, the geopolitical interest arising during last decades, the geo-economic transformation and the ample debate on environment and on sustainability development: these are the main aspects that stimulate geographical reflexions about Svalbard islands. The entire arctic area is of strategic importance by many external countries, or at least by those which aspire to a geopolitical role of a certain relevance. Svalbard an interesting example of economic transition from coal-export dependency to a post-modern form of tourism, that have token significant forms and dimensions respecting the principles of environmental sustainability. The remarkable aspect regards the success of an example of auto regulation of responsibility that derives from a culture of respect of the public common good and in based on a appear as a total symbiosis between social components and the surrounding environment. Finally, Svalbard are a fundamental territory for polar-studies activity concentrated in NyÅlesund bay where numerous scientific bases are involved in climate studies.